Fructan metabolising enzymes in rhizophores of Vernonia herbacea upon excision of aerial organs - Asega, Amanda Francine (Plant physiology and biochemistry : PPB, 2004)
The activities of fructan metabolising enzymes and fructan contents are reported for rhizophores of Vernonia herbacea (Vell.) Rusby induced to sprouting by shoot excision. The activities of fructan exohydrolase (1-FEH), sucrose: sucrose fructosyltransferase (1-SST), fructan: fructan fructosyltransferase (1-FFT) and invertase (INV) and the fructan contents were analysed every 3-4 days for 1 month by colorimetric and chromatographic methods. Sprouting of new shoots started on day 9. 1-FEH activity increased after day 13 and reached its maximum value 20 days after shoot excision. A gradual decrease in 1-SST activity was detected between days 3 and 9. 1-FFT activity exhibited fluctuations throughout the experimental period and a peak of activity for invertase was detected 9 days after shoot excision. Variation in fructan contents in vivo included a decrease until day 13 after which, levels remained practically unchanged. Fructan depolymerization and sprouting are concomitant processes in V. herbacea and can be induced by shoot excision at any phenological phase. 1-FEH and 1-FFT seemed to act in a concerted way to catalyse fructan depolymerization, while 1-SST was inhibited, possibly due to interruption of sucrose supply to rhizophores from the aerial organs